Two new species of Ophiostomatales (Sordariomycetes) associated with the bark beetle Dryocoetes alni from Poland - Strzałka, Beata; Jankowiak, Robert; Bilański, Piotr; Patel, Nikita; Hausner, Georg; Linnakoski, Riikka; Solheim, Halvor (Pensoft Publishers, 2020)
Bark beetles belonging to the genus Dryocoetes (Coleoptera, Curculionidae, Scolytinae) are known vectors of fungi, such as the pathogenic species Grosmannia dryocoetidis involved in alpine fir (Abies lasiocarpa) mortality. Associations between hardwood-infesting Dryocoetes species and fungi in Europe have received very little research attention. Ectosymbiotic fungi residing in Ceratocystiopsis and Leptographium (Ophiostomatales, Sordariomycetes, Ascomycota) were commonly detected in previous surveys of the Dryocoetes alni-associated mycobiome in Poland. The aim of this study was to accurately identify these isolates and to provide descriptions of the new species. The identification was conducted based on morphology and DNA sequence data for six loci (ITS1-5.8S, ITS2-28S, ACT, CAL, TUB2, and TEF1-α). This revealed two new species, described here as Ceratocystiopsis synnemata sp. nov. and Leptographium alneum sp. nov. The host trees for the new species included Alnus incana and Populus tremula. Ceratocystiopsis synnemata can be distinguished from its closely related species, C. pallidobrunnea, based on conidia morphology and conidiophores that aggregate in loosely arranged synnemata. Leptographium alneum is closely related to Grosmannia crassivaginata and differs from this species in having a larger ascomatal neck, and the presence of larger club-shaped cells.
Keywords: Bark beetle; Scolytidae; Ceratocystiopsis; Leptographium; ophiostomatoid fungi; fungal taxonomy; new species description